The Use of Audio Visual Media to Improve Learning Outcomes of Asmaul Husana Material at Jeumpa 3 Public Elementary School - Viati, Nanda (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the learning outcomes of grade V students of SDN 3 Jeupa, Southwest Aceh Regency on Asmaul Husna material through the use of audio-visual media. The background of the research departs from the low learning outcomes of students who are still below the Minimum Completeness Criteria, as well as the use of learning methods that tend to be monotonous. This study uses the Classroom Action Research (PTK) approach which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of the study were 21 students, consisting of 11 males and 10 females. Data was collected through observation of learning activities, learning outcome tests, and documentation, then analyzed in a qualitative descriptive manner. The results of the study show that the application of audio-visual media is able to increase students' motivation, activeness, and understanding of the material. In the first cycle, the average student learning outcomes only reached 69 with a completion percentage of 43%. After improvements were made in cycle II, the average learning outcome increased to 82 with a classical completion percentage of 86%. Thus, the use of audio-visual media has proven to be effective in improving student learning outcomes in Asmaul Husna material. This research provides an implication that teachers need to utilize innovative learning media to make learning more interesting and meaningful.